Influences of Ultrasonic Assisted Pectin Extraction with Hydrochloric and Citric Acid from Kluai Namwa (Musa ABB cv.) on Yields Analyzed by Taguchi Method - Chakrabandhu, Yasinee; Osiriphun, Sukhuntha; Jinsiriwanit, Siriwat; Leksawasdi, Noppol; Intipunya, Pilairuk; Ratchtanapan, Pornchai; Ngeunkaew, Koranid; Tananchai, Kamolpat (Asian Health, Science and Technology Reports, 2019)
Waste of Kluai Namwa is mostly left in Thailand. Pectin extraction methods have been used to be modified. Ultrasound- assisted extraction (UAE) methods were recently known to be involved in green technology. Pectin extraction was determined the conditions of the highest percentage yield of pectin from the banana peel using ultrasound under the limitation of devices. Ultrasound conditions were set under 400 watts-maximum limit with percentage of the amplitude 60 80 and 100. Extraction times were varied at 5 10 and 15 minutes. In this study, the types of acids were compared between hydrochloric and citric acid. The Taguchi method, orthogonal array was used to support systematic experiment and maximizes the desired results. The most important factor affecting the pectin yield was acid types (factor A, 30.03%) followed by exposure time (factor C, 23.18%) and ultrasonic amplitude (factor C, 19.36%). Pectin yield predictive equation was computed by statistical software as - 0.07 - 2.19 Acid type + 0.0529 Ultrasonic amplitude + 0.235 Exposure time, R-Sq (adj) = 82.7%. The results showed that the highest yield was obtained by using the condition which gave 100% of amplitude and 15 minutes of extraction time. The obtained pectin yield was 7.88%. The degree of esterification was 37.78% showed low methoxyl percentage (MeO%) as 6.17%.